Examining the influence of phychosocial factors and entrepreneurship centre towards entrepreneurial quality among undergraduate students in Malaysia - Noor Muthmainnah Hamdul Hadi; Universiti Sultan Zainal Abidin . Faculty of Business and Management (2016)
It is widely accepted that entrepreneurship represents a real engine of economic development globally. In Malaysia, entrepreneurship also found to be a significant role to prosper the economic growth by contributing to the job creation. innovation and market development. Thus, government always has taking steps to promote the creation and development of entrepreneurs. The attention also was given by the government at tertiary level in order to encourage university students in venturing into entrepreneurship. The entrepreneurship programs offered by local universities either in forms of core subject or embedded in the curriculum are aimed to produce as many as possible student entrepreneurs. evertheless, the impact was not satisfactory when it fails to attract majority of the graduates to venture into entrepreneurship activities after study. This phenomenon attracts a question why universities failed to produce student entrepreneurs like other institutions such as technical and other vocational training center. Thus, this study attempts to achieve three objectives. First, to examine the relationship between psychosocial factors; social supports, university experiences and rnentoring towards entrepreneurial quality among students. Secondly to analyze the mediating effect of the role of entrepreneurship centre on psychosocial factor towards entrepreneurial quality among students. Third is to investigate the most predictor of entrepreneurial quality among students. Various relevant literatures were reviewed until a conceptual framework of the relationship between psychosocial factors, role of entrepreneurship centre and entrepreneurial quality among students was produced. In order to achieve the research objectives, four public universities in Malaysia were selected to involve in this tudy, which included Universiti Teknologi Mara (UiTM), Universiti Utara Malaysia (UUM), Universiti Malaysia Kelantan (UMK) and Universiti Malaysia I erlis (UniMAP). The sample for this study involved final year students of Bachelor Business and Administrative at the four public universities in Malaysia. Reliability test, descriptive statistics, correlation analysis and regression analysis were used to analyze the data. The finding shows that there is a positive relationship between psychosocial factors; social supports, university experiences and mentoring on entrepreneurial quality. The result also indicates there is a positive relationship between the role of entrepreneurship centre and entrepreneurial quality among students. On the other hand, the role of entrepreneurship centre is a partial mediator of the relationship between social support and university experience to entrepreneurial quality. However, the relationship between mentoring and entrepreneurial quality was fully mediated by the role of entrepreneurship centre. Meanwhile, the result of regression analysis showed that social supports were the key factors that influence entrepreneurial quality among public university in Malaysia. To conclude. the findings provide insights that benefit the higher education institutions in designing curriculum or training that would potentially enhance entrepreneurial quality among public university students in Malaysia.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Findings and results -- 5. Discussions and conclusions
Thesis (Degree of Master of Science in Management) - Universiti Sultan Zainal Abidin, 2016
Includes bibliographical references (p. 105-116)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Business and Management -- Dissertations; Success in business; Dissertations, Academic